Literature Study of The Potential of Moringa Oleifera Leaves Powder Supplementation to Enhance The Coloration of Ornamental Fish - Grace Angelica; Mas Rizky Anggun Adipurna Syamsunarno; Aziiz Mardanarian Rosdianto (Jurnal Perikanan dan Kelautan, 2020)
Efforts to maintain good ornamental fish are by providing the quality of feed. The quality of feed is assessed from the best nutritional content as well as economical and can increase the brightness of ornamental fish. Feeds with pigment carotenoids complexes are known to be the main sources of ornamental fish skin pigmentation. A literature study was conducted to explore the benefits of Moringa oleifera leaves powder to improve the color of ornamental fish through carotenoid content. Based on the results of literature studies, supplementation of these natural products has potentially elevated the color brightness of ornamental fish at carotenoid dose 520 mg/kg. Further research on the potential and formulation of M. oleifera leaves powder supplementation impact color brightness of ornamental fish in vivo is very important to explain the mechanism of carotenoids in influencing the physical color brightness of ornamental fish